Effect of low-oxygen-concentration layer on iron gettering capability of carbon-cluster ion-implanted Si wafer for CMOS image sensors. (15th January 2018) - Onaka-Masada, Ayumi; Nakai, Toshiro; Okuyama, Ryosuke; Okuda, Hidehiko; Kadono, Takeshi; Hirose, Ryo; Koga, Yoshihiro; Kurita, Kazunari; Sueoka, Koji
Abstract: The effect of oxygen (O) concentration on the Fe gettering capability in a carbon-cluster (C3 H5 ) ion-implanted region was investigated by comparing a Czochralski (CZ)-grown silicon substrate and an epitaxial growth layer. A high Fe gettering efficiency in a carbon-cluster ion-implanted epitaxial growth layer, which has a low oxygen region, was observed by deep-level transient spectroscopy (DLTS) and secondary ion mass spectroscopy (SIMS). It was demonstrated that the amount of gettered Fe in the epitaxial growth layer is approximately two times higher than that in the CZ-grown silicon substrate. Furthermore, by measuring the cathodeluminescence, the number of intrinsic point defects induced by carbon-cluster ion implantation was found to differ between the CZ-grown silicon substrate and the epitaxial growth layer. It is suggested that Fe gettering by carbon-cluster ion implantation comes through point defect clusters, and that O in the carbon-cluster ion-implanted region affects the formation of gettering sinks for Fe.